Eräiden turvelajiemme kemiallisesta kokoomuksesta ja sen vaikutuksesta niiden polttoarvoon - Soveri, U. (Agricultural and Food Science, 1948)
The aim of this work is to give the reader a general picture of the main constituents of some varieties of peat found in Finland, and the significance of these constituents in fuel peat. Attention has primarily been focussed on the thermodynamically important constituents of peat, i.e. bitumen, water soluble organic substances, proteins, substances hydrolyzable with acid (cellulose, hemicelluloses), substances unhydrolyzable with acid (lignin and the products of the decomposition of lignin) and ash. The method of analysis chiefly used was that of Waksman and Stevens, which was. however, somewhat abbreviated. The following varieties of peat were used: 8 samples of pure Sphagnum peat (S-peat), 7 samples of Carex peat (C-peat) of which three contained some wood waste (LC-peat) and one some unchanged Carex rostrata, 4 samples of Amblystegium Carex peat (AC-peat) and a profile consisting of Sphagnum peat containing some Eriophorum peat (Er S-peat). The samples were gathered in Northern Finland. Ash: After discussion of the factors influencing the ash content of peat and the composition of the ash, the results of the peat analyses carried out are considered. The ash of the acid soluble fraction contains mainly sesqui-oxides while the ash of the insoluble residue chiefly consists of SiO2 and silicates (secondary ash) (Table 2). Table 3 shows that: 1) The lightly humified surface peat (H1 —H2) generally contains considerably more water soluble ash and less acid soluble ash than the more humified peat; 2) The acid soluble ash constituents seem to increase with the dept (decreasing acidity and precipitation of metal hydroxides); 3) Analyses of AC-peat show more acid soluble and less insoluble ash than Sand C-peat (this agrees with the higher pH-value of AC-peat). Bitumen. The nature of bitumen, the methods of estimating the bitumen content of peat, and of previous investigations are discussed. The bitumen content of 30 samples of Er S-peat was determined by extraction with a benzene-alcohol mixture (1 : 1). The results are set out in Fig. T. Table 4 shows the results of the bitumen determinations according to Waksman’s and Stevens’ method. The following conclusions can be drawn: 1) AC-peat contains considerably less bitumen than S-peat and C-peat, and C-peat contains more bitumen than S-peat; 2) The results confirm the old theory that the bitumen content increases more markedly with the degree of humification in S-peat than in C-peat; 3) AC-peat has the smallest ether fraction (30.9 %) expressed in percentage of the total bitumen content, S-peat a somewhat higher (40.5 %), and C-peat the highest percentage (50.8 %). These results agree with those obtained by other scientists from analysis of Scandinavian material, but not with results obtained by American scientists with European and American material (see table 5). Other organic constituents of peat. Fig. 1 shows the trend of change in the chemical composition which occurs in the humification of pure S-peat and S-peat containing some Eriophorum peat. Tables 6 and 7 show that the changes in the C-peat and S-peat follow the same general trend. The most obvious and thermodynamically most important difference in the chemical composition of these two kinds of peat is the considerably greater content of unhydrolyzable substance in the C-peat. Table 8 shows the difference in the composition of C-peat and S-peat. According to this, S-peat would appear to contain about twice as much cellulose and hemi-cellulose as C-peat. S-peat also contains a greater proportion than C-peat of the A-fraction, which is that part of the acid soluble fraction that is not cellulose, hemicellulose or protein but consists mainly of humic acids. In both kinds of peat the least humified samples contained the largest proportion of A-fraction. The expression »Free crude protein» in table 7 means the protein quantity which is equivalent to the water and acid soluble quantity of nitrogen. The cellulose and hemicellulose content of C-peat have been found to be somewhat larger than those mentioned in the literature. The variations in the quantities of water soluble substances in all the samples of peat investigated correspond on the whole with the results published by other scientists. The influence of the chemical composition of peat on its calorific value. Table 9 shows the gross calorific values of the various fractions. The values have been obtained by determining the total gross calorific value, the gross calorific value of the residual fraction, and the gross calorific values of two ether and alcohol soluble fractions. These values have then been used in calculating the gross calorific value of the water and acid soluble fractions and of the bitumen fraction. The probable changes in the calorific values of both the ether and alcohol soluble substances, due to humification, have thus not been accurately taken into consideration. That C-peat has a higher calorific value than S-peat in spite of its higher ash content, is probably due to the following facts: 1) The bitumen content of C-peat is higher 2) The bitumen of C-peat contains more ether soluble substances 3) C-peat contains more proteins, which have a higher calorific value than hydrocarbons 4) C-peat contains more carbonaceous substances (lignin etc.) that are unhydrolyzable with acids. 5) The substances in C-peat which are unhydrolyzable with acids have higher calorific values than those of S-peat. Thus the calorific value of peat does not depend only on the quantities of the various fractions in peat forming plants and the corresponding varieties of peat, but also on the variations in the chemical composition of these fractions.